Sad fetus syndrome: a rare case report - K., Mamatha; Gawda, Lekha Prakash (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Gestational trophoblastic disease (GTD) is a condition that develops from abnormal proliferation of placental trophoblasts. A rare division of GTD is a partial mole with a co-existing live fetus-a condition also referred to as “sad fetus syndrome” We report a rare case of a 24-year-old, primigravida with 26 weeks of gestational age with single live intrauterine gestation coexisting with partial molar pregnancy who had a spontaneous preterm delivery at 27 weeks. The post-natal period was uneventful and patient was followed up till βhcg normalised. The diagnostic challenges and dilemma associated with the management of molar pregnancies with an apparently normal fetus, especially in the second trimester, remains challenging.